Residential energy efficiency and European carbon policies: A CGE-analysis with bottom-up information on energy efficiency technologies - Brita Bye; Taran Fæhn; Orvika Rosnes (Statistics Norway, Research Department, 2015)
While the introduction and reformation of climate policy instruments take place rapidly in Europe, the knowledge on how the instruments interact lags behind. In this paper we analyse different interpretations of the 2030 climate policy goals for residential energy efficiency and how they interact with targets for restricting CO2 emissions. We focus on Norway, whose climate and energy policies are integrated with those of the EU. As we account for investment costs of improving energy efficiency we find substantial welfare costs of energy efficiency policies, particularly when interacting with carbon pricing. Rebound effects within households are small, but economy-wide indirect rebound is significant because energy-intensive, trade-exposed (EITE) industries expand. As residential energy use consists mainly of carbon-free electricity, this expansion of EITE-industries leads to increased total CO2 emissions.
Keywords: D58; Q43; Q48; 330; Carbon policies; Energy efficiency policies; General Equilibrium analysis; Rebound effects